Transboundary pipelines and the Arctic: legal issues - Vylegzhanin, Alexander N.; Moskwa, Urzula (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2016)
In the universal sources of modern international law, the regime of cross-border pipelines is set out only in general terms. It is true even regarding the 1982 UN Convention on the Law of the Sea, which provides the most developed regulations relating to laying such pipelines. National legal rules applicable to laying pipelines, however, in practice provide for additional requirements which go beyond conventional rules. Relevant national laws are often based on international environmental law, including multilateral environmental treaties. Existing regional treaties providing regulations on cross-border pipelines are most often also of a framework nature.